(3OhQ GdeSJfOGJ ai JfajP GdHjY GdOhdi ddHVGFY (B/ s - (3MfGf UahJ fGLi YHOGdbGOQ HgfSGhis; (3SejMI GdbdjhHi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JfGhdJ gPg GdQSGdI ehVhY OhQ GdeSJfOGJ ai JfajP GdHjY GdOhdi ddHVGFY hbO YGdLJ gPG GdehVhY ai KdGKI CHhGH, JfGhdfG ai GdHGH GdChd OhQ GdeSJfOGJ ai JfajP GdJRGei GdHGFY HGdJSdje hfbd GdedcjI ef NdGd TQhW SdGeI GdeSJfOGJ, hef Ke JfGhdfG GdeSJfOGJ GdeeKdI ddHVGYI cCOGI ddJSdje hOhQgG ai JfajP GdJRGeGJ GdHGFY(B. (3hai GdHGH GdKGfi JfGhdfG JWHjbGJ JaUjdjI dTQhW SdGeI GdeSJfOGJ ai aUdjf, JMOKfG ai GdChd Yf eSJfOGJ Gdfbd, CeG GdaUd GdKGfi abO NUUfGg deSJfOGJ GdJCejf Ydi GdHVGFY hGdaGJhQI GdJLGQjI hGdeSJfOGJ GdEVGajg(B. (3CeG ai GdHGH GdKGdK JfGhdfG ajg OhQ GdeSJfOGJ ai JfajP GdJRGe GdeTJQi HCOGA GdKef ai aUdjf, JMOKfG ai GdChd Yf GdeHGOF GdYGeI daMU GdeSJfOGJ heYjGQg, CeG GdKGfi Yf ehba GdHfc ef GdeSJfOGJ GdeNGdaI(B. s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2015s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B347-364s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3GdHjY GdOhdj ddHVGFY s; (3GdeSJfOGJ s; (3SfO GdTMf s; (3GdJRGe GdHGFY Hfbd GdedcjI s; (3SdGeI GdeSJfOGJ s; (3eSJfOGJ Gdfbd s; (3GdJRGe GdeTJQj HCOGA GdKef s; (3GdaGJhQI GdJLGQjI s; (3aMU GdeSJfOGJ s; (3QaV GdeSJfOGJ s; (3GdJShjI GdeTQhWI s; (3GdENWGQ HGdQaVs; (3eSJfOGJ Gdfbd GdLhj hGdHQj s; (3eSJfOGJ GdJCejf Ydi GdHVGFY s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs